2013
DOI: 10.1111/bcpt.12079
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Attenuates Isoflurane‐Induced Acute Memory Impairments in Aged Rats

Abstract: Abstract:Melatonin is an endogenous hormone with neuroprotective effects. Melatonin levels in elderly patients are reduced after surgeries that require anaesthesia. Whether reduced melatonin levels are important for postoperative cognitive dysfunction (POCD) remains unclear. Here, we investigated the effects of melatonin on cognitive dysfunctions induced by isoflurane and mechanisms underlying these effects. Seventy-two 20-month-old Sprague-Dawley rats were randomly divided into six groups (n = 12). These grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Although it remains unspecified what function to which diurnal changes in hippocampal neuronal morphology contribute, many studies have reported that dendritic structure of hippocampal neurons is associated with hippocampus‐dependent learning and memory, or cognitive behaviors (Pyter et al, ; Workman et al, ; Crupi et al, ; Walton et al, ); daily variation is observed in some hippocampal functions and hippocampus‐dependent behaviors (Chaudhury et al, ; Ruby et al, ; Tamai et al, ; Takahashi et al, ; Rawashdeh et al, ). Long‐term administration of melatonin modulates hippocampal neuronal plasticity (Rennie et al, ; Ramírez‐Rodríguez et al, , ; Crupi et al, ) and improves cognitive performance (Kilic et al, ; Crupi et al, ; Liu et al, ). In addition to these chronic effects, this study suggests the importance of acute effects of melatonin on daily and seasonal fluctuations in hippocampal physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Although it remains unspecified what function to which diurnal changes in hippocampal neuronal morphology contribute, many studies have reported that dendritic structure of hippocampal neurons is associated with hippocampus‐dependent learning and memory, or cognitive behaviors (Pyter et al, ; Workman et al, ; Crupi et al, ; Walton et al, ); daily variation is observed in some hippocampal functions and hippocampus‐dependent behaviors (Chaudhury et al, ; Ruby et al, ; Tamai et al, ; Takahashi et al, ; Rawashdeh et al, ). Long‐term administration of melatonin modulates hippocampal neuronal plasticity (Rennie et al, ; Ramírez‐Rodríguez et al, , ; Crupi et al, ) and improves cognitive performance (Kilic et al, ; Crupi et al, ; Liu et al, ). In addition to these chronic effects, this study suggests the importance of acute effects of melatonin on daily and seasonal fluctuations in hippocampal physiology.…”
Section: Discussionmentioning
confidence: 99%
“…13,14) In brief, rats were placed in a temperature-controlled, transparent anesthetic chamber with inflow and outflow hoses. Isoflurane (Baxter Healthcare, Deerfield, IL, U.S.A.) was delivered in 100% oxygen at 2 L/min using agent specific vaporizers.…”
Section: Animals and Experimental Groupsmentioning
confidence: 99%
“…The underlying mechanisms for this include neuroinflammation and AD-related neurotoxicity [15,16]. We previously reported that isoflurane exposure affected hippocampal melatonin receptors, which could be stabilized with melatonin pre-treatment [17]. Considering the role of hippocampal MT 2 in AD and related cognitive impairment [10], we hypothesized that MT 2 signalling may also play a role in isoflurane-induced neurotoxicity and cognitive impairment.…”
mentioning
confidence: 99%